From to Jihad to Salam in Pursuit of Political Change: A Perspective based on Qur’ānic Sources - Dr. Muqtedar Khan (Journal of Islamic and Religious Studies, 2017)
The political reality of many countries in the Muslim World is untenable and reforms and change is absolutely necessary. This article argues that use of force and violence for political change is making things worse as one can witness in Syria and Iraq. The article advances a Qur’ānic perspective on the desirability of peace as a goal and peaceful means as instruments of change. The article acknowledges that the Qur’ānic sanction for use of force to defend religious freedom prcludes the advocacy of pacifism but nevertheless the article does make a strong case for privileging peace over use of force.